Comportamento mecânico e evolução microestrutural do cobre comercialmente puro submetido ao forjamento multidirecional - Maria Elisa Landim Nassif (2019)
The severe plastic deformation (SPD) processes have been developed to increase the material strength by introducing a high dislocation density in the material leading to its work hardening, and also decreasing the average grain size and rearranging the dislocations into high misorientation boundaries. Among the techniques of SPD, Multi-directional Forging (MDF) imposes deformation through repeated compression in three successive and orthogonal directions of the material. However, free compression MDF introduces lateral barreling on samples, justifying the use of confined MDF: a new method studied by ALMEIDA (2017) and FLAUSINO et al. (2019) that occurs with a confined channel die. The present work evaluates the mechanical behavior and microstructural evolution of Copper subjected to low and high strain amplitude (∆ε=0.075 e ∆ε=0.5) in the first cycle of deformation (one, two and three passes) and up to 48 passes with ∆ε=0.075 and up 6 passes with ∆ε=0.5. The results show that confined MDF causes the work hardening of Copper leading to steady state flow stresses due to dynamic recovery processes, with higher flow stresses for higher strain amplitudes, but the values are smaller than those achieved by uniaxial compression. The processing caused an increase in dislocation density and a decrease in the average grain size in both amplitudes, though the grain refinement is more pronounced and the kinetics is faster for high strain amplitudes. It was also observed that mechanical strength of Copper is related to the average grain size, dislocation density and to the fraction of high and low angle grain boundaries of the material after processing. The study indicates that the low amplitude MDF enhances the initial stages of dynamic recovery and that the strain path influences in the mechanical response of the material. Besides that, the influence of multidirectional deformation on mechanical properties of Copper was confirmed, since dynamic recovery is favored by loading in reverse directions.